Systematic Mapping in Mobile Learning Topics Based on Bibliometric Analysis - Adlina, Firza Luthfia (Journal of Educational Technology and Instruction, 2022)
The study aims to reverse the trend in mobile learning research through bibliometric analysis by focusing on authors, publications, keywords, and countries. The data from 2011-2021. This research uses various applications that can assist bibliometric analysis, namely Publish or Perish (PoP), VosViewer, and Ms. Excel. Bibliometric analysis shows that most of the countries doing mobile learning are Malaysia, Indonesia, India, United States, Saudi Arabia, Spain, Australia, Taiwan, Turkey, and China. According to the keyword “Mobile learning’, “M-Learning”, “E-Learning”, and “Mobile Device” are the most keywords is platform, mobile application, m-learning application, mobile learning technology, multimedia, and educational process. It was found citing largest analyzed that research by Emran, Mezhuyev, and Kamaludin (2015) is 268 citation. And the last, was found the highest number of authors is shown in 3, the number of authors is 877 with percentages 88% researchers who collaborite in mobile learning research.